CHARACTERIZATION OF HYDATID CYST FLUID FROM RUMINANTS AND HUMANS BY SDS-PAGE IN PUNJAB, PAKISTAN - A. A. Latif; A. Tanveer; A. A. Anjum; M. A. Ali; M. S. Rana; M. R. Khan; M. S. Ahmad (Journal of Animal and Plant Sciences, 2013)
Polypeptide analysis of purified hydatid cyst fluid (HCF) from ruminants (sheep, goat, cattle, buffalo and camel) and human beings was performed by sodium dodecyl sulphate polyacrylamide gel (12%) electrophoresis (SDS-PAGE) under reduced conditions. HCFs from different species revealed variable segregation pattern of proteins not only within the different hosts of the parasites but also in different types of HCF. In fertile HCF, five to three protein bands were observed in different intermediate hosts of the parasite viz., buffalo (269, 166, 89, 59 and 25kDa), goat (46, 29, 22 and 18kDa), sheep (209, 138 and 63kDa), cattle (269, 89 and 59kDa), camel (195, 166 and 123kDa) and human beings (195, 138, 21 and 6kDa). In sterile HCF of different species, less number of protein bands was found as compared to fertile cysts. The two protein bands were observed in sterile HCF collected from camel (195 and 141kDa), cattle (27 and 18 kDa), buffalo (43 and 27kDa) and human being (30 and 21kDa), whereas only one polypeptide band found in sheep (123kDa) and goat (78kDa). SDS-PAGE analysis of hydatid cyst fluid collected from different intermediate hosts of Echinococcus granulosus exhibited variable profiles of proteins. The present study suggests that SDS-PAGE alone is not a reliable diagnostic tool both in ruminants and human, it should be coupled with recent molecular techniques.
Keywords: Echinococcus granulosus; polypeptides; SDS-PAGE; human beings; ruminants; fertile and sterile cysts